APLIKASI PENDUKUNG PEMBELAJARAN MATEMATIKA PADA MASA COVID-19 - Putri Prastanti; Anggun Badu Kusuma (JURNAL MathEdu (Mathematic Education Journal), 2021)
This article discusses supporting applications for learning mathematics during the Covid-19 pandemic. The corona virus or Covid-19 is currently sweeping the world, including Indonesia, participating in influencing the world of education where the teaching and learning process is usually carried out face-to-face in classrooms due to the Covid-19 pandemic, the teaching and learning process must be done through distance learning (online ). Technology-based learning media that is commonly used are computers. To support computers, we need software in the form of applications. With the application, it is hoped that teachers and students will be more optimal in carrying out teaching and learning activities online. An important application to support mathematics learning is because mathematics is abstract and is often considered difficult by students. Some of these applications are Geogebra, Matlab, Wingeom, Microsoft Math 3.0 and Microsoft Math 4.0. This study aims to assist teachers and students in using applications that support mathematics learning.